Perencanaan Bahan Ajar Teks Anekdot dengan Pendekatan Keterampilan Abad 21 pada Kelas X Sekolah Menengah Kejuruan - Imrotin Imrotin; Saefuddin Famsah; Sri Wahyuni (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
The 21st-century skills are the answer to the world of education in welcoming the industrial era 4.0. Indonesian language teaching materials for the Vocational High School (SMK) level also need to adapt to this approach. Synchronizing the SMK curriculum with industry certainly brings advantages for preparing anecdotal text teaching materials, especially animation skills. This research and development using the 4D method, seek to create prototypes of teaching materials that apply 21st-century skills assisted by Google Sites. The research stages consist of initial research and information gathering, product foundation and planning, and product format development. The product testing stage is not carried out. Teachers have difficulty completing the material because learning hours are often used for vocational activities. The application of 21st-century skills in anecdotal teaching materials is as follows: (1) critical thinking is applied to activities to identify structure and language; (2) communication is carried out by presenting the idea to be uploaded through social media; (3) collaboration with group activities in writing anecdotes based on comic strips; and (4) creativity and innovation in compiling anecdotal texts based on comic strips in the order given.